Factors influencing the Nucleation and Morphology of Crystallographic Type Etch Pits in Pure Iron. - Spink, Geoffrey (My University, 1969)
Etch pits can be produced in iron whose shape reflects the crystallography of the crystal. It is shown that pit morphology can be adequately predicted from an orientation dependent dissolution theory. The influence of an air-formed surface oxide film on pit nucleation and morphology is demonstrated.
Keywords: Nucleation; Morphology; Czystallographic; Etch Pits; pure iron